The Possible Applications of Endophytic Fungi - Parmida Aleahmad; Leila Ebrahimi* (Iranian Society of Pharmacognosy, 2023)
Endophytic fungi are microorganisms that colonize plants during their entire, or a significant part of their life cycle without any symptoms, establishing a symbiosis association. They are abundant in plants and have been reported in various tissues, such as roots, stems, leaves, flowers, and fruits. In recent years, research on the beneficial use of endophytic fungi has increased worldwide. These fungi have the ability to protect plants from both biotic and abiotic stresses through different mechanisms. They also improve water and nutritional status leading to increased growth and fitness of host plants. Endophytes are rich sources of bioactive and secondary metabolites, making them promising candidates for the development of compounds with anticancer, antibiotic, antiviral, antidiabetic, and other pharmacological activities. Moreover, they produce various enzymes that hold economic and environmental potential for industrial applications. This study explored the diverse effects of endophytic fungi in agriculture, biofuels, medicine, industry and bioremediation.